Ensino religioso em tempos de pandemia: desafios para os docentes da rede municipal de João Pessoa – PB - Vasconcelos, Cleyton Carlos Silva de (2023)
The present study analyzed the main challenges faced and the experiences experienced by professors of the Religious Education (RE) discipline in the city of João Pessoa – PB in the pandemic period between March 2020 and December 2021. More specifically, I sought to reflect on the configuration of RE in context of Paraíba, its difficulties and possibilities; I sought to identify the contributions of RE, amid the COVID-19 pandemic, for professors; I also intended to reveal the challenges of RE for professors and also identify possibilities for strengthening RE as a curricular component in the city of João Pessoa – PB. My interest in the topic arose from my experience while RE professor in that municipality, where I am currently working. The pandemic period and the urgency of social isolation brought many challenges for professors. Given all the changes imposed by the pandemic, what challenges did RE professors face? How did these professors perceive such challenges and face them through the emergence of remote professors, which emerged as an alternative for continuing the teaching-apprenticeship? Therefore, the investigation was based on analyzing such challenges. In methodological terms, the research is qualitative in nature. A field research was carried out, whose data were collected through semi-structured interviews with RE professors in the municipality, and a phenomenological interpretation approach was used to understand the object of study. The data were analyzed using the content analysis technique with the interpretation of the phenomenological method, and the data was presented using categories identified in the analysis of the collected material. We also highlight that a documentary research was carried out, from which some important documents were analyzed for the problematization of education in the municipal network in the highlighted period, such as: Municipal Education Plan (2015-2025), Municipal Education Policy of João Pessoa (2021-2024), among others. For the theoretical foundation of this study, among the main authors used, José Octávio de Mello, Gracileide Alves da Silva, Maria José Holmes and Marinilson Barbosa da Silva, among others, stood out. It was possible to notice that professors made similar reports regarding the challenges faced during the pandemic period, such as the urgency of using new technologies; the precariousness of technological access for both students and many professors. Added to this was fear and anguish due to the severity and threat of the virus. These are, therefore, difficulties and challenges faced from a psychosocial, technological, and also pedagogical/didactic aspect. I believe that this research made significant contributions to strengthening the RE component and its professors.